An Order Release Control Mechanism Based on self-Adaptive Neural Fuzzy Inference System and Theory of Constraints - Chuandong Zhan; Jiangming Kan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Order release is the key premise for the semiconductor wafer fabrication system to perform well, which is also one of the paramount significant components in the scheduling strategies. Most order release strategies merely have focused on the workloadbut failed in considering the remarkable influence oncycletime of common orders that is brought by unexpectedrushones.In this paper an on-linemechanismbased on Theory of Constraintsfor lot releaseusingself-Adaptive Neural Fuzzy Inference System modelswas presentedwhich is able to adjust the release rhythmdynamicallyaccording to dynamics of fabs.In our approach, an ANFIS model was established to predict the ratiobetweenhotand common lotsin wafer fabto perform adjustments on the order release schedule in advance.Simulated experimentsbased on the HP24 model were carefully performed and experimental results proved a better performance of common lotsthan original TOC on a large scale, especially when it comes to the situation of disturbance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3488